Hierarchical Hollow Co/N-C@NiCo2O4 Microsphere as an Efficient Bi-functional Electrocatalyst for Rechargeable Zn–Air Battery - Song, Yuke; Xie, Wenfu; Li, Shijin; Guo, Jian; Shao, Mingfei (Frontiers in Materials, 2019)
Zn–air batteries (ZABs) have drawn extensive attention for portable and wearable electronic devices owing to their high theoretical specific energy density and low cost. However, due to the dense packing under high mass loading, the mass/charge diffusion is seriously hindered, making their practical performance with high power density, and energy density difficult to sustain. Herein, we reported an efficient bi-functional electrocatalyst of Ni-Co mixed metal oxides incorporated with cobalt/nitrogen-doped carbon with hierarchical hollow nanostructure (H-Co/N-C@NiCo2O4). Benefiting from the advantages of this structure and composition, the H-Co/N-C@NiCo2O4 exhibits superior electrocatalytic activity and long-time durability for both oxygen reduction reaction (ORR) and oxygen evolution reaction (OER). The potential gap between half-wave potential in ORR and overpotential at a current density of 10 mA cm−2 in OER reaches 0.8 V, much smaller than that of most reported bi-functional electrocatalysts. Moreover, H-Co/N-C@NiCo2O4 is constructed as an air electrode for rechargeable ZAB, delivering a high power density and long cycling stability. The good linear relationship between the power density and various mass loading of H-Co/N-C@NiCo2O4 on the electrode demonstrates that the performance has been well-maintained even under high dense packing of catalysts, which offers a new pathway for the practical applications in ZAB.